Feeding activity of Eisenia andrei and Enchytraeus albidus under different soil moisture regimes assessed by the bait-lamina test - Gilda Dell’Ambrogio; Sophie Campiche; Janine W. Y. Wong; Mathieu Renaud; Christina Lüthi; Inge Werner; Benoit J. D. Ferrari (PLoS ONE, 2026)
The bait-lamina test is an easy and efficient method to quantify the feeding activity of soil invertebrates. However, under natural conditions, feeding activity is influenced by environmental factors such as soil moisture content, whose effects on test outcomes remain insufficiently quantified, complicating interpretation. In this study, we optimized the bait-lamina test under laboratory conditions, to assess the influence of soil moisture content on feeding activity of the earthworm Eisenia andrei and the enchytraeid Enchytraeus albidus , using LUFA 2.2 standard soil (LUFA Speyer, Speyer, Germany) as a substrate. Feeding activity increased linearly with increasing soil moisture until an optimal moisture content, which was 52% of the maximum water holding capacity (WHC) for earthworms, and between 49 and 68% WHC for enchytraeids. Above these optima, feeding activity was reduced and was less dependent on soil moisture. The increase in feeding activity up to the peak was described by different slopes for the two species. Earthworms consumed the bait faster (on a per unit weight basis) than enchytraeids. Among the two species, the relationship established for E. albidus was the more similar to the response obtained in field conditions. Within the range of soil moistures considered by the model, our results demonstrate that feeding activity is positively correlated with soil moisture for two important soil invertebrates, although this increase, the optimal soil moisture content, and the speed of bait consumption are species-dependent. The model produced provides a first quantitative framework describing these relationships and can serve as a basis for future studies testing its applicability across different soil types. Such research would represent a first step for normalizing results from bait lamina tests under field conditions.